Effect of the Substituent of the Cation of N-Octylpyridinium Hexafluorophosphate in the Electrical and Electrochemical Response of Carbon Paste Electrodes Modified with These Ionic Liquids - Aguirre-Quintana, M; Aguirre-Quintana, M; Fuenzalida-Ortiz, F; Fuenzalida-Ortiz, F; Arce-Escobar, R; Arce-Escobar, R; Aravena-Ponce, D; Aravena-Ponce, D (Elsevier Ltd, 2017)
A series of N-octylpyridinium hexafluorophosphate ionic liquids (ILs), ascribed as ROpyPF6, where Opy = N-octylpyridinium and R are the substituents –OCH3, –CH3, –CF3 and –CN at the para position of the cation, were characterized and employed as binders in carbon paste electrodes (CILEs) to evaluate the electron donating or withdrawing effects of the substituent of the cation in physical and electrochemical properties of these CILEs. Substituents strongly affect the melting point of the ILs, the electric properties of the CILEs measured by electrochemical impedance spectroscopy, and the electrochemical behavior measured by the response for an outer-sphere reaction (ferro/ferricyanide redox couple) and for an inner-sphere irreversible reaction (oxidation of sulfite). Results show that ILs can be separated in two different groups: those that have withdrawing electron substituents and those that have donating-electron substituents. OpyPF6 has a behavior similar to those that have withdrawing electron substituents. Carbon paste electrode prepared with mineral oil as binder (CPE) has a very different behavior and is described for comparison purposes only. Results show that the ILs with withdrawing electron substituents have more polarized cations (a more localized positive charge) acquiring a slight ionic character in comparison to the ILs with donating substituents. The electron withdrawing effect modifies the hydrogen-fluorine interactions and also the electrostatic interactions between anion and cation, modifying the electric and electrochemical response of the CILEs, resulting in more conductive and homogeneous surfaces. © 2017 Elsevier Ltd